Post-prandial Remnant Lipoprotein Metabolism in Sitosterolemia - Inazu, Akihiro; Kawashiri, Masa-aki; Yamagishi, Masakazu; Nohara, Atsushi; Mabuchi, Hiroshi; Nomura, Akihiro; Tada, Hayato (Journal of Atherosclerosis and Thrombosis, 2018)
Aim: We aimed to clarify post-prandial accumulation of remnant-like particles (RLP) in patients with sitosterolemia.Methods: Oral fat tolerance test cream (Jomo Shokuhin, Takasaki, Japan) 50 g was given per body surface area (m2); blood sampling was performed at 2 h intervals up to 6 h. Plasma lipoprotein fractions and RLP fractions were determined in four sitosterolemic subjects with double mutations in ATP-binding cassette (ABC) sub-family G member 5 or member 8 (ABCG5 or ABCG8) gene (mean age=18 yr, median low-density lipoprotein cholesterol [LDL-C]=154 mg/dL), six heterozygous carriers (mean age=31 yr, median LDL-C=105 mg/dL), and five subjects with heterozygous familial hypercholesterolemia (FH, mean age=32 yr, median LDL-C=221 mg/dL). The incremental area under curve (iAUC) of lipids, including LDL-C, apolipoprotein B-48 (apoB48), RLP cholesterol (RLP-C), and RLP triglyceride (RLP-TG) were evaluated.Results: After oral fat load, there was no significant difference of the iAUC of LDL-C between sitosterolemia and heterozygous FH, whereas the iAUC of apoB48 was significantly larger in the sitosterolemic subjects compared with that of heterozygous FH (2.9 µg/mL×h vs. 1.3 µg/mL×h, p＜0.05). Under these conditions, the iAUCs of RLP-C and RLP-TG levels were significantly larger in the sitosterolemic subject compared with those of heterozygous FH (9.5 mg/dL×h vs. 5.7 mg/dL×h, p＜0.05; 149 mg/dL×h vs. 40 mg/dL×h, p＜0.05, respectively), whereas those of heterozygous carriers were comparable with those with heterozygous FH.Conclusions: Post-prandial lipoprotein metabolism in sitosterolemia appeared to be impaired, leading to their elevation in serum sterol levels. (UMIN Clinical Trials Registry number, UMIN000020330)